THE MEANING OF UMMATAN WASATAN AND YOGA IN RELATION TO RELIGIOUS MODERATION: A Comparative Study of Q.S. Al-Baqarah [2]: 143 and Bhagavad Gita 6.17 Roland Barthes' Semiotic Perspective - Saniti, Moh Halir Ridla (Islamuna: Jurnal Studi Islam, 2024)
ABSTRACT Religious moderation is a solution step in the midst of differences that exist in a multicultural nation to anticipate disharmony in society. This article samples the concept of religious moderation offered by Islam as a Samawi religion in Q.S. Al-Baqarah [2]: 143 which is represented in the word ummatan wasaá¹an and the concept of religious moderation offered by Hinduism as an Ardi religion in Bhagavad Gita 6.17 which is represented in the word yoga. Although both were born from different wombs and different contexts, there must be similarities in certain respects. Therefore, to find the differences as well as the similarities, Roland Barthes' semiotics is used to explore the different aspects of language as well as their historical contexts. There are two important findings in this article first, the linguistic review shows that the word ummatan wasaá¹an in Islam refers to a group that is moderate, just and becomes â€²uswatun á¸¥asanah. While the word yoga in Hinduism is moderation, balance, and spiritual endeavour; secondly, the two scriptures have similarities and differences both based on origin and context, meaning, main focus, and practical application. Keywords: Religious moderation, comparison, semiotics, Roland Barthes ABSTRAK Moderasi beragama merupakan sebuah langkah solutif di tengah perbedaan yang ada dalam sebuah bangsa yang multikultural untuk mengantisipasi disharmonisasi dalam masyarakat. Artikel ini mengambil sampel konsep moderasi beragama yang ditawarkan oleh Islam sebagai agama Samawi dalam Q.S. Al-Baqarah [2]: 143 yang terepresentasi dalam kata ummatan wasaá¹an dan konsep moderasi beragama yang ditawarkan oleh agama Hindu sebagai agama Ardi dalam Bhagavad Gita 6.17 yang terepresentasi dalam kata yoga. Meskipun keduanya lahir dari rahim yang berbeda dan konteks yang berbeda, pasti terdapat kesamaan dalam beberapa hal tertentu. Maka untuk menemukan sisi perbedaan sekaligus persamaan keduanya, penggunaan semiotika Roland Barthes digunakan untuk menelusuri perbedaan aspek bahasa sekaligus konteks historis keduanya. Terdapat dua temuan penting dalam artikel ini pertama, tinjauan kebahasaan menunjukkan bahwa kata ummatan wasaá¹an dalam Islam menunjuk pada kelompok yang moderat, adil dan menjadi â€²uswatun á¸¥asanah. Sedangkan kata yoga dalam agama Hindu adalah moderasi, keseimbangan, dan usaha spiritual; kedua, kedua kitab suci tersebut memiliki persamaan dan perbedaan baik berdasarkan asal-usul dan konteks, pemaknaan, fokus utama, serta pengaplikasian secara praktis. Kata Kunci: Moderasi Beragama, Komparasi, Semiotika, Roland Barthes